ARCHIPELAGIC STATE RESPONSIBILITY ON ARMED ROBBERY AT SEA - Putri, Siti Noor Malia (Indonesian Journal of International Law, 2017)
Recent hijackings to Indonesian ships on the southern waters of the Philippines have raised alarming concerns not only from the involving states but also other countries in the region. Such crimes at sea frequently occur in the area of the coastal states in this case archipelagic states such as Indonesia and the Philippines. This privilege as archipelagic states automatically extends their sovereignty and jurisdiction to enforce their national legislations. As a corollary, responsibility to ensure the security and capacity to protect and supervise territory should be carefully examined when looking at the current situations. This paper examines the responsibility of archipelagic states in the event of sea armed robbery within their jurisdiction.